Influence of Transfusion on the Risk of Acute Kidney Injury: ABO-Compatible versus ABO-Incompatible Liver Transplantation - Yu, Je Hyuk (J Clin Med, 2019)
ABO-incompatible liver transplantation (ABO-i LT) is associated with a higher risk of acute kidney injury (AKI) compared to ABO-compatible liver transplantation (ABO-c LT). We compared the risk of AKI associated with transfusion between ABO-c and ABO-i living donor liver transplantation (LDLT). In 885 cases of LDLT, we used a propensity score analysis to match patients who underwent ABO-c (n = 766) and ABO-i (n = 119) LDLT. Baseline medical status, laboratory findings, and surgical- and anesthesia-related parameters were used as contributors for propensity score matching. AKI was defined according to the “Kidney Disease Improving Global Outcomes” criteria. After 1:2 propensity score matching, a conditional logistic regression analysis was performed to evaluate the relationship between the intraoperative transfusion of packed red blood cells (pRBCs) and fresh frozen plasma (FFP) on the risk of AKI. The incidence of AKI was higher in ABO-i LT than in ABO-c LT before and after matching (after matching, 65.8% in ABO-i vs 39.7% in ABO-c, p < 0.001). The incidence of AKI increased in direct proportion to the amount of transfusion, and this increase was more pronounced in ABO-i LT. The risk of pRBC transfusion for AKI was greater in ABO-i LT (multivariable adjusted odds ratio (OR) 1.32 per unit) than in ABO-c LT (OR 1.11 per unit). The risk of FFP transfusion was even greater in ABO-i LT (OR 1.44 per unit) than in ABO-c LT (OR 1.07 per unit). In conclusion, the association between transfusion and risk of AKI was stronger in patients with ABO-i LT than with ABO-c LT. Interventions to reduce perioperative transfusions may attenuate the risk of AKI in patients with ABO-i LT.